Cloud Height Daytime Variability From DSCOVR/EPIC and GOES-R/ABI Observations - Delgado-Bonal, A.; Marshak, A.; Yang, Y.; Oreopoulos, L. (Frontiers in Remote Sensing, 2022)
One of the largest uncertainties in climate sensitivity predictions is the influence of clouds. While some aspects of cloud formation and evolution are well understood, others such as the diurnal variability of their heights remains largely unexplored at global scales. Aiming to fill that fundamental gap in cloud knowledge, this paper studies the daytime evolution of cloud top height using the EPIC instrument aboard the DSCOVR satellite, complemented by coincident cloud height retrievals by GOES-R’s ABI instrument. Both datasets indicate that cloud height exhibits a minimum around midday for low clouds with amplitudes between 250 and 600 meters depending on the season. The two datasets also agree that high clouds exhibit a contrasting behavior with steady increase of cloud height from morning to evening. We investigate dependences on the type of underlying surface, finding that the amplitude of the diurnal cycles is weaker over ocean than over land for both EPIC and ABI retrievals. We also find a positive correlation between cloud fraction and height over ocean which turns negative over land for low clouds, while for high clouds the correlation is largely positive.